Scalp biopsy identifies systemic amyloidosis presenting as isolated telogen effluvium: A case report - Sutherland, Rory A (SAGE Open Med Case Rep, 2019)
AL amyloidosis is a complication of B-cell dyscrasias and multiple myeloma, manifest as deposition of antibody fragments in many different organs, including the skin. We describe a rare case of this systemic disease which presented with isolated scalp alopecia. Further investigation led to the diagnosis of an occult plasma-cell dyscrasia, showing the benefit of including systemic amyloidosis in the differential diagnosis of alopecia. The biopsy finding of cutaneous amyloidosis should prompt further workup to exclude an underlying pathology.